Molecular Dynamics Simulation Of Liquid Na2O - Le , Thế Vinh; Duong , Công Hiệp; Nguyen, Minh Quân; Pham, Khắc Hùng (Journal of Technical Education Science, 2008)
Molecular dynamic simulation has been done to investigate the local structure of liquid sodium oxide (Na2O) at 2330 K using the Born–Mayer type pair potential with boundary periodic conditions. Clear evidence was found of structural network consisting mainly of tetrahedral NaO4. The microstructure of our system is analyzed through partial pair correlations, coordination numbers, and angle distributions. Void and its characteristics were examined and discussed here.